Responses to supplementation by dairy cows given low pasture allowances in different seasons 1. Pasture intake and substitution - Penno, J. W.; Macdonald, K. A.; Holmes, Colin W.; Davis, S. R.; Wilson, G. F.; Brookes, Ian M.; Thom, E. R. (Cambridge, 2006)
Two factorial experiments were designed to determine the effects of stage of lactation, and season of the year, on cow responses to supplementary feeding. These experiments were conducted over consecutive years with 128 high genetic merit multiparous Holstein-Friesian cows in early, mid and late lactation in spring, summer, autumn and winter. At each stage of lactation, and in each season of the year, cows were offered a restricted pasture allowance (25 to 35 kg dry matter (DM) per cow per day), either unsupplemented (control) or supplemented with 50 MJ metabolizable energy (ME) per cow per day in experiment 1 and 80 MJ ME per cow per day in experiment 2. Two different supplements were offered, namely, rolled maize grain (MG) and a mixture of foods (BR) formulated to nutritionally balance the diet. In experiment 2, a fourth treatment consisting solely of a generous pasture allowance (60 to 75 kg DM per cow per day, AP) was introduced. Offering MG and BR increased DM intake (DMI). At the restricted pasture allowance, increasing total ME allowance (MEA) by offering supplementary foods increased ME intake (MEI) by 0.68 (s.e. 0.047) MJ per extra MJ ME offered. This highly significant (P < 0.001) linear relationship was consistent across seasons, and did not diminish at higher MEA. In experiment 2, cows in early lactation had lower substitution rates than mid and late lactation cows irrespective of season. Substitution rate was higher when higher pasture allowance or quality of pasture on offer enabled the unsupplemented cows to achieve higher DMI from pasture than at other times of the year. These results suggest that one of the key factors determining the intake response to supplementary foods is pasture allowance. Within spring calving dairying systems, the largest increases in total DMI per kg of supplement offered is likely when offering supplements to early lactation cows grazing restricted allowances of high quality pasture.
Keywords: Dairy cows; Grazing; Pasture intake; Substitution; Supplementary feeding; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300400 Animal Production::300403 Animal nutrition